An integrated approach to modelling energy policy in South Africa: Evaluating carbon taxes and electricity import restrictions - Channing Arndt; Rob Davies; Sherwin Gabriel; Konstantin Makrelov; Bruno Merven; Faaiqa Salie; James Thurlow (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
We link a bottom-up energy sector model to a recursive dynamic computable general equilibrium model of South Africa in order to examine two of the country's main energy policy considerations: (i) the introduction of a carbon tax and (ii) liberalization of import supply restrictions in order to exploit regional hydropower potential. Our results suggest substantial reductions in the country's greenhouse gas emissions when these two policy changes are jointly implemented (relative to business-as-usual baseline scenario). Moreover, the two policies impose essentially no cost to economic growth, although there is a 1 per cent reduction in employment. From our analysis we conclude that a regional energy strategy, anchored in hydropower, represents a potentially inexpensive approach to reducing emissions in South Africa. Moreover, combining carbon taxes with a removal of import restrictions lessens the burden of adjustment on politically sensitive and economically important sectors.
Keywords: O55; Q43; Q47; Q49; 330; integrated bottom-up model; the integrated MARKAL-EFOM system; computable general equilibrium; carbon tax; South Africa